Grade of eosinophilia versus symptoms in patients with dysphagia and esophageal eosinophilia. Issue 8 (10th September 2015) - Larsson, H.; Norder Grusell, E.; Tegtmeyer, B.; Ruth, M.; Bergquist, H.; Bove, M.
Summary: The aim of this study was to assess whether the symptom severity and health‐related quality of life (HRQL) of patients with dysphagia and esophageal eosinophilia correlate with disease activity as expressed by the number of eosinophils in the esophageal mucosa. This study included newly diagnosed ( n = 58) or relapsed patients ( n = 7), where 40% were diagnosed in connection with esophageal bolus impaction. The mean age was 45 years (19–88), and 74% were men. Symptoms and HRQL were recorded using the Watson Dysphagia Scale (WDS), the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire – Oesophageal Module 18 and the Short Form‐36 Questionnaire. Histological samples gathered from the proximal and distal esophageal mucosa were stained using both hematoxylin and eosin (HE) and an immunohistochemical (IHC) technique against 'Eosinophil Major Basic Protein, ' and the peak number of eosinophils per high‐power field was assessed. More eosinophils were detected after IHC staining than HE staining ( P < 0.001). No correlation was found between symptoms or the HRQL and the number of eosinophils. However, higher numbers of eosinophils at the proximal esophagus were found in patients with concomitant bolus impaction (IHC P < 0.05 and HE P < 0.05) and could serve as a risk marker.